2016
DOI: 10.1016/j.kint.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Megalin and cubilin in proximal tubule protein reabsorption: from experimental models to human disease

Abstract: Proximal tubule protein uptake is mediated by 2 receptors, megalin and cubilin. These receptors rescue a variety of filtered ligands, including biomarkers, essential vitamins, and hormones. Receptor gene knockout animal models have identified important functions of the receptors and have established their essential role in modulating urinary protein excretion. Rare genetic syndromes associated with dysfunction of these receptors have been identified and characterized, providing additional information on the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
317
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 362 publications
(333 citation statements)
references
References 121 publications
(154 reference statements)
9
317
0
7
Order By: Relevance
“…We extended these studies to include comprehensive analysis of LDLR-related proteins in rat liver, brain and kidney (Fig. 1, labeled 4 and Suppl. Dataset 2), and we were able to confirm four out of the four predicted glycosites in the XX-C6XXXTC1-XX linker regions of LDLR, three out of five in VLDLR, seven out of eight in LRP1, and eight out of 10 in LRP2 (rat LRP2 has three fewer predicted glycosites than human between LA1-2, 23-24, and 30-31).…”
Section: O-glycosites In the Linker Regions Of Class A Repeats Of Ldlmentioning
confidence: 99%
See 1 more Smart Citation
“…We extended these studies to include comprehensive analysis of LDLR-related proteins in rat liver, brain and kidney (Fig. 1, labeled 4 and Suppl. Dataset 2), and we were able to confirm four out of the four predicted glycosites in the XX-C6XXXTC1-XX linker regions of LDLR, three out of five in VLDLR, seven out of eight in LRP1, and eight out of 10 in LRP2 (rat LRP2 has three fewer predicted glycosites than human between LA1-2, 23-24, and 30-31).…”
Section: O-glycosites In the Linker Regions Of Class A Repeats Of Ldlmentioning
confidence: 99%
“…The LDLR superfamily includes the VLDL receptor (VLDLR), LDLR-related protein 1 (LRP1), LDLR-related protein 1B (LRP1B), LDLR-related protein 2 (LRP2 or megalin) and LDLR-related protein 8 (LRP8 or ApoER2), as well as more distantly related receptors such as the Sortilin-related receptor (SORLA) (1). These members also have important roles in cardiovascular diseases as well as neurodegenerative and proteinuric renal diseases (3)(4). The ectodomains of LDLR-related proteins share characteristic structural features including LDLR-type A repeats (LA) (complement-like cysteine-rich ligand binding repeats), EGF-like repeats, and YWTD beta-propeller domains (1).…”
mentioning
confidence: 99%
“…Thus, it is suggested that Cd reabsorption is mediated by receptor-mediated endocytosis, involving the multi-ligand receptors, megalin and cubulin Thevenod and Wolff 2016). These two multi-ligand receptors are localized to the apical membrane of PT cells, and they are responsible for reabsorption of the all proteins, notably albumin and MT, present in the glomerular filtrate (Nielsen et al 2016).…”
Section: Cadmium -From Dinner Plate To Kidney Cell Toxicitymentioning
confidence: 99%
“…Megalin has predominantly been studied in the kidney proximal tubular epithelium. [14][15][16] Here, it localizes to the apical membrane as well as the endolysosomal apparatus of proximal tubular cells and mediates reabsorption of many different ligands from the glomerular ultrafiltrate. [14][15][16] Megalin has furthermore been shown to be expressed in both cytotrophoblasts and syncytiotrophoblasts of human placenta and, here, suggested to function as a nutrient receptor and mediate uptake of nutrients from the maternal bloodstream (similar to its functions in the kidney).…”
Section: Research-article2016mentioning
confidence: 99%
“…[14][15][16] Here, it localizes to the apical membrane as well as the endolysosomal apparatus of proximal tubular cells and mediates reabsorption of many different ligands from the glomerular ultrafiltrate. [14][15][16] Megalin has furthermore been shown to be expressed in both cytotrophoblasts and syncytiotrophoblasts of human placenta and, here, suggested to function as a nutrient receptor and mediate uptake of nutrients from the maternal bloodstream (similar to its functions in the kidney). [17][18][19][20][21] However, the function of placental megalin has not been systematically investigated in suitable models, and the suggestions regarding the role of megalin in human placenta therefore remain purely speculative.…”
Section: Research-article2016mentioning
confidence: 99%